EFFORTS TO REALIZE STUDENTS’ DECISIONS IN CHOOSING TO STUDY AT PTS IN ORDER TO INCREASE STUDENTS’ SATISFACTION (Studies at PTS in Semarang City) - Rokh Eddy Prabowo (Proceedings Education and Language International Conference, 2017)
The purpose of this study was to find the factors that influence the students’ decisions in choosing to attend lectures at Private Higher Education (PTS). These factors are the managements’ efforts of PTS to increase customer satisfaction, in this case students’ satisfaction. This is an exploratory study, because the respondent was free to answer questions according to their experience. The respondents were taken from 11 private universities in Semarang City set by purposive random sampling technique. The data is processed by using descriptive approach. The results of the research indicated that there were 13 factors that affected students to choose to study at PTS. Those factors were: brand image of PTS (18.5%), not accepted at PTN, Police/Military Academy (17%), the place is close to home and strategic (16%), family and friends (15%), a low cost/affordable (8%), managed by religious foundation (7%), compliance with students’ interest (6%), eager to increase knowledge (4%), accreditation status (2%), there are afternoon/week-end classes (2%), desire to be an entrepreneur (2%), managed by the foundation of UNDIP alumni (1.5%), and full facilities and good environment (1%). When these factors were coupled with the concept of the marketing mix of products and services, there are only four relevant factors: places, people, price, and facilities/physical appearance. Based on these data, in order to increase students’ satisfaction the managements of PTS should improve the brand image, the relationships with students’ family, and maintain the affordable tuition fee. Keywords: marketing mix, brand image, customer satisfaction, Private Higher Education (PTS)